Volatile organic compounds characterized from grapevine (Vitis vinifera L. cv. Malbec) berries increase at pre-harvest and in response to UV-B radiation - Gil, Mariana; Bottini, Ambrosio Rubén; Berli, Federico Javier; Pontin, Mariela Ana; Silva, Maria Fernanda; Piccoli, Patricia Noemí (2018)
Ultraviolet-B solar radiation (UV-B) is an environmental signal with biological effects in plant tissues. Recent investigations have assigned a protective role of volatile organic compounds (VOCs) in plant tissues submitted to biotic and abiotic stresses. This study investigated VOCs in berries at three developmental stages (veraison, pre-harvest and harvest) of Vitis vinifera L. cv. Malbec exposed (or not) to UV-B both, in in vitro and field experiments. By Head Space-Solid Phase Micro Extraction–Gas Chromatography–Electron Impact Mass Spectrometry (HS-SPME–GC–EIMS) analysis, 10 VOCs were identified at all developmental stages: four monoterpenes, three aldehydes, two alcohols and one ketone. Monoterpenes increased at pre-harvest and in response to UV-B in both, in vitro and field conditions. UV-B also augmented levels of some aldehydes, alcohols and ketones. These results along with others from the literature suggest that UV-B induce grape berries to produce VOCs (mainly monoterpenes) that protect the tissues from UV-B itself and other abiotic and biotic stresses, and could affect the wine flavor. Higher emission of monoterpenes was observed in the field experiments as compared in vitro, suggesting the UV-B/PAR ratio is not a signal in itself.